PERAN KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA GURU SMP NEGERI - Thamrin Abdullah (Universitas Pakuan, 2014)
Research on the Relationship of Principal Leadership and Motivation Work with Teacher Job Satisfaction aims to examine the relationship between two independent variables, namely the Principal Leadership (X1) and Work Motivation Teacher (X2), the dependent variable is Teacher Job Satisfaction (Y) The population of this research is all the Junior High School teachers who were civil servants in the district Ciwandan Cilegon. The samples in this study were drawn from a population of 89 teachers. There is a positive and highly significant relationship between the Principal Leadership and Motivation Teacher Working together with Teacher Job Satisfaction with the regression equation Y = 12.512 + 0.389 X1 + 0.504 X2. Keywords: Teacher Job Satisfaction, leadership and work motivation Principal.